Effects of Chitosan, NaOCl, and EDTA Irrigation Solutions on the Cyclic Fatigue Resistance of Three Nickel-Titanium Endodontic Rotary Files: An In Vitro Study - Wisam S Salloom; Biland M.S Shukri (Wolters Kluwer Medknow Publications, 2022)
Introduction The goal of this study was to compare the impact of NaOCl, EDTA, and chitosan on the cyclic fatigue of 2Shape, HyFlex EDM, and RACE EVO. Methods A total of 120 new 2Shape (n = 40), HyFlex EDM (n = 40), and RACE EVO (n = 40) files were subdivided randomly into four groups (n = 10): Group (A) with no immersion, Group (B) with immersion in 5.25% NaOCl for 5 min, Group (C) with immersion in 17% EDTA for 5 min, and Group (D) with immersion in 0.2% chitosan for 5 min. The files were rotated in an artificial canal with a 5 mm radius and a 60° curvature at body temperature until they fractured, and the number of cycles to fracture was measured. ANOVA test and Tukey post-hoc test were used to analyze the data. Results Immersion of the files in NaOCl, EDTA, or chitosan solutions had no significant effect on the number of cycles to fracture (P > 0.05). Conclusion The irrigation solutions did not have any influence on the cyclic fatigue of the tested files.